Reluctance in world politics : why states fail to act decisively - Destradi, Sandra (Bristol University Press, 2023)
Why do international actors, including powerful states, often fail to develop clear foreign policies and instead adopt indecisive, 'muddling-through' approaches? This book develops a concept and a theory of reluctance in world politics. Applying it to the study of regional crisis management by India, Germany and Brazil, it finds that reluctance emerges when governments fail to devise clear foreign policy preferences and face competing international pressures. The study of reluctance in world politics sheds new light on some of the most pressing problems of our time, from weak crisis management to cooperation deficits in global governance.